The Role of Reconstructive Surgery for Treating Pressure Injuries – A Review of Literature - Martyna Łukasiewicz; Magdalena Grotowska; Maria Wydro; Aleksandra Strawińska (Quality in Sport)
Pressure injuries (PIs) represent a significant global health challenge, affecting approximately 10.8% of the European population in 2019. Their development is primarily attributed to ischemia and tissue necrosis resulting from prolonged pressure. According to the NPIAP classification, PIs are categorized into four stages, with surgical intervention predominantly indicated for stage III and IV ulcers. Reconstructive surgery encompasses various techniques, with debridement (the removal of necrotic tissue) being the most frequently performed procedure. An essential component of the healing process is negative pressure wound therapy (NPWT), which facilitates oxygen delivery to deeper tissue layers and promotes faster regeneration. Promising outcomes have also been observed with the use of regional flaps, particularly in the management of large bedsores and cases where other options are no longer viable. Despite advancements in surgical treatments, challenges such as graft rejection and high recurrence rates persist. The selection of the surgical approach should be guided by the patient’s overall health status and the specific characteristics of the ulcer. Effective management of PIs is critical for preventing prolonged hospitalizations and mitigating the risk of hospital-acquired infections, thereby significantly improving patients' quality of life.